Inflammatory Bowel Disease: Genetics, Epigenetics, and Pathogenesis - Loddo, Italia; Romano, Claudio (Frontiers in Immunology, 2015)
Inflammatory Bowel Diseases (IBDs) are complex, multifactorial disorders characterized by chronic relapsing intestinal inflammation. Although aetiology remains largely unknown, recent research has suggested that genetic factors, environment, microbiota and immune response are involved in the pathogenesis. Epidemiological evidence for a genetic contribution is defined: 15% of patients with Crohn’s Disease (CD) have an affected family member with IBD, and twin studies for CD have shown 50% concordance in monozygotic twins compared to less than 10% in dizygotics. The most recent and largest genetic association studies, which employed genome-wide association data for over 75,000 patients and controls, identified 163 susceptibility loci for IBD. More recently, a trans-ethnic analysis, including over 20,000 individuals, identified an additional 38 new IBD loci. Although most cases are correlated with polygenic contribution toward genetic susceptibility, there is a spectrum of rare genetic disorders that can contribute to early onset IBD (before 5 years) or very early IBD (before 2 years). Genetic variants that cause these disorders have a wide effect on gene function. These variants are so rare in allele frequency that the genetic signals are not detected in genome-wide association studies of patients with IBD. With recent advances in sequencing techniques, approximately 50 genetic disorders have been identified and associated with IBD-like immunopathology. Monogenic defects have been found to alter intestinal immune homeostasis through many mechanisms. Candidate gene resequencing should be carried out in early-onset patients in clinical practice. The evidence that genetic factors contribute in small part to disease pathogenesis confirms the important role of microbial and environmental factors. Epigenetic factors can mediate interactions between environment and genome. Epigenetic mechanisms could affect development and progression of IBD. Epigenomics is an emerging field, and future studies could provide new insight into the pathogenesis of IBD.